Polycyclic aromatic hydrocarbons (PAHs) in the environment of Beijing, China: Levels, distribution, trends and sources. Issue 1 (2nd January 2018) - Zhai, Yuanzheng; Yin, Zhihua; Zhao, Xiaobing; Zhang, Junjun; Zuo, Rui; Wu, Jin; Yang, Jie; Teng, Yanguo; Wang, Jinsheng
ABSTRACT: Polycyclic aromatic hydrocarbons (PAHs) have become a major type of persistent organic pollutant (POPs) in the world. To well understand the occurrence, spatial distribution and source apportionment of 16 PAHs in different media in Beijing, a comprehensive study was conducted based on 337 obtained and subsequently selected samples in four specific media, including soil, road dust, surface water and atmosphere covering sampling time spanning from 2005 to 2014. Mean concentrations of Σ16 PAHs in soils (878.5 μg/kg) decreased from inner city to exterior areas with different land uses decreased in the order of industrial estate (2510 μg/kg)>educational area (1331 μg/kg)>Park (783 μg/kg)>cultivated (650 μg/kg)>roadside (583 μg/kg)>residential (568 μg/kg)>green area (478 μg/kg)>forest area (125 μg/kg). Meanwhile, PAHs concentrations in branch roads were slightly higher than trunk roads and mainly concentrated in urban areas (1136 μg/kg). Affected by industrial and residential areas, PAHs concentrations in downstream surface rivers were much higher than upstream surface rivers (475 ng/L). Due to strong mobility, PAHs concentrations in atmosphere were not equally distributed around the study area (157.59 ng/m 3 ). The result of source apportionment determined by diagnostic ratios method indicated PAHs in multiple media in Beijing are mainly from coal and biomass combustion.